Supporting student journals - Betz, Sonya; Crema, Leonora; Hall, Robyn (My University, 2020)
Student journals provide undergraduate and graduate students with the opportunity to publish and establish an academic footprint, while also learning about and participating in peer-review processes and the production of online publications. Librarians and library staff are supporting student journals in a variety of ways. The following brief details current activities of libraries in Western Canada and more broadly supporting such efforts, while suggesting recommendations and considerations for those looking to start or build upon existing initiatives in this area.
Keywords: open access; undergraduate research; academic publishing